2021
DOI: 10.24967/teksis.v6i1.1231
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Model Tarikan Dan Bangkitan Kendaraan Di Daerah Kecamatan Pemulutan Kabupaten Ogan Ilir

Abstract: Fungsi dan tata guna lahan pada suatu daerah tentunya akan memenghasilkan bangkitan dan tarikan perjalanan dari dan ke daerah tersebut. Tak terlepas dari hal itu, termasuklah lahan pada daerah pedesaan. Dengan adanya perubahan tata guna lahan, kebutuhan serta karakteristik transportasi juga akan berubah pula. Maka dari itu, dilakukanlah penelitian untuk mendapatkan model bangkitan dan tarikan kendaraan akibat perubahan tata guna lahan di kecamatan Pemulutan. Berdasarkan data-data yang dikumpulkan, didapat mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The ground check location locations are determined by identifying points on the land cover map. The Slovin formula was used to calculate the number of samples (Mauliana et al 2021):…”
Section: Data Analysis Land Use and Land Cover Change (Lulc) And The ...mentioning
confidence: 99%
“…The ground check location locations are determined by identifying points on the land cover map. The Slovin formula was used to calculate the number of samples (Mauliana et al 2021):…”
Section: Data Analysis Land Use and Land Cover Change (Lulc) And The ...mentioning
confidence: 99%
“…The results showed that the greatest influence of the attraction of movement is influenced by the area of the building with the best regression model using the stepwise method with the result Y = 14.455 + 0.005 X2 where X2 is the total area of the building. Analysis of Trip Attraction and Generation Model of Vehicles in Pemulutan District, Ogan Ilir Regency (Mauliana et al, 2021). The results showed that using the multiple linear regression approach with the stepwise method resulted that the current entry and exit routes had not affected the activity of the activity system in Jalan Buaya, Pemulutan District, Ogan Ilir Regency.…”
Section: Introductionmentioning
confidence: 98%
“…As a buffer, these areas are also experiencing growth both in terms of economy and population. [13] [14] The increase in population in the buffer zone of Jakarta is due to some people who work or do activities in Jakarta prefer to live in these buffer zones. [15][16] [17] Ciputat area in South Tangerang City is one of the areas directly adjacent to Jakarta, Depok, and Bogor.…”
Section: Introductionmentioning
confidence: 99%